Adhesive film for circuit connection, circuit connection structure, and method for producing same
Patent Information
- Application Number
- CN202380057896.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-10
- Filing Date
- 2023-08-01
- Publication Date
- 2025-03-07
Smart Images

Figure CN119585379A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an adhesive film for circuit connection, a circuit connection structure and a method for manufacturing the same. Background Art
[0002] In the past, an anisotropic conductive film in which conductive particles are dispersed in an adhesive film was used for connection between a liquid crystal display and a tape carrier package (TCP), connection between a flexible printed circuit board (FPC) and a TCP, or connection between an FPC and a printed circuit board. Specifically, circuit components are bonded to each other through a circuit connection portion formed by an adhesive film for circuit connection, and electrodes on the circuit components are electrically connected to each other via conductive particles in the circuit connection portion, thereby obtaining a circuit connection structure. In addition, in the case of mounting a semiconductor silicon chip on a substrate, a so-called chip on glass (COG) installation in which the semiconductor silicon chip is directly mounted on the substrate is also performed instead of the conventional wire bonding, and an anisotropic conductive film is also used in the COG installation (for example, refer to Patent Document 1).
[0003] Previous technical literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2016-054288 Summary of the invention
[0006] Technical issues to be solved by the invention
[0007] In anisotropic conductive films, it is difficult to control the fluidity during connection, and when the semiconductor chip is connected to the substrate (when heat and external force are applied), the adhesive component overflows from the circuit connection portion, resulting in the localization of conductive particles in the circuit connection portion. If the conductive particles are localized in the circuit connection portion, the conductive particles will be densely packed between adjacent circuits to form a short circuit, which may cause malfunction.
[0008] Furthermore, if the fluidity of the anisotropic conductive film is insufficient, the resin repellency between the connection circuits may decrease, and the connection resistance may increase.
[0009] Therefore, a main object of the present invention is to provide an adhesive film for circuit connection that can suppress localization of conductive particles and reduce connection resistance even when heat and external force are applied.
[0010] Means for solving technical problems
[0011] As a result of studying to solve the above problems, the present inventors have found that by using a specific resin as a thermoplastic resin, localization of conductive particles can be suppressed even when an external force is applied, thereby reducing connection resistance, thereby completing the present invention.
[0012] The present invention provides an adhesive film for circuit connection according to [1] to [9], a method for manufacturing a circuit connection structure according to
[10] , and a circuit connection structure according to
[11] .
[0013] [1] An adhesive film for circuit connection, comprising: a first adhesive layer containing conductive particles and a thermoplastic resin; and a second adhesive layer provided on the first adhesive layer, wherein the thermoplastic resin comprises a resin in which at least a portion of the hydroxyl groups in a phenoxy resin is modified with a group represented by the following formula (1) or the following formula (1A).
[0014]
[0015] [In formula (1), R 1 represents a hydrogen atom or a methyl group, x represents an integer of 2 to 6, and y represents an integer of 1 to 6. * represents a bonding position to an oxygen atom derived from a hydroxyl group. ]
[0016]
[0017] [In formula (1A), R 1 , x, y and * have the same meanings as above. *1 and *2 represent the bonding positions to the carbon atoms of other free radical polymerizable groups.]
[0018] [2] The circuit-connecting adhesive film according to [1], wherein the thickness of the first adhesive layer is 5 μm or less, and the ratio of the thickness of the first adhesive layer to the average particle size of the conductive particles is 0.50 or more.
[0019] [3] The circuit-connecting adhesive film according to [1] or [2], wherein the first adhesive layer further contains a cured product of a photocurable resin component and a first thermosetting resin component, and the second adhesive layer further contains a second thermosetting resin component.
[0020] [4] The circuit-connecting adhesive film according to [3], wherein the photocurable resin component contains a radical polymerizable compound and a photoradical polymerization initiator.
[0021] [5] The circuit-connecting adhesive film according to [3] or [4], wherein the first thermosetting resin component and the second thermosetting resin component contain a cationically polymerizable compound and a thermal cationic polymerization initiator.
[0022] [6] The circuit-connecting adhesive film according to [5], wherein the cationically polymerizable compound is at least one selected from the group consisting of oxetane compounds and alicyclic epoxy compounds.
[0023] [7] The adhesive film for circuit connection according to [5] or [6], wherein the thermal cationic polymerization initiator is a salt compound having an anion containing boron as a constituent element.
[0024] [8] The circuit connection adhesive film according to any one of [3] to [7], further comprising: a third adhesive layer provided on the side of the first adhesive layer opposite to the second adhesive layer and containing a third thermosetting resin component.
[0025] [9] The circuit-connecting adhesive film according to [8], wherein the third thermosetting resin component contains a cationically polymerizable compound and a thermal cationic polymerization initiator.
[0026]
[10] A method for manufacturing a circuit connection structure, comprising the following steps: placing the circuit connection adhesive film described in any one of [1] to [9] between a first circuit component having a first electrode and a second circuit component having a second electrode, and performing thermal compression bonding on the first circuit component and the second circuit component to electrically connect the first electrode and the second electrode to each other.
[0027]
[11] A circuit connection structure comprising: a first circuit component having a first electrode; a second circuit component having a second electrode; and a circuit connection portion arranged between the first circuit component and the second circuit component to electrically connect the first electrode and the second electrode to each other, wherein the circuit connection portion comprises a cured product of the circuit connection adhesive film described in any one of [1] to [9].
[0028] Effects of the Invention
[0029] According to the present invention, an adhesive film for circuit connection is disclosed, which can suppress the localization of conductive particles even when heat and external force are applied, and can reduce the connection resistance. In addition, according to the present invention, a circuit connection structure using such an adhesive film for circuit connection and a manufacturing method thereof are disclosed. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a schematic cross-sectional view showing one embodiment of the adhesive film for circuit connection.
[0031] Figure 2 This is a schematic cross-sectional view showing one embodiment of a circuit connection structure.
[0032] Figure 3 This is a schematic cross-sectional view showing one embodiment of a method for producing a circuit-connected structure. Figure 3 (a) and Figure 3 (b) is a schematic cross-sectional view showing each step. DETAILED DESCRIPTION
[0033] Hereinafter, embodiments of the present invention will be described in detail, but the present invention is not limited to the following embodiments.
[0034] In this specification, the numerical range shown by "~" indicates that the numerical values recorded before and after "~" are included as the minimum and maximum values, respectively. In the numerical range recorded in stages in this specification, the upper limit or lower limit of the numerical range of a certain stage can be replaced by the upper limit or lower limit of the numerical range of other stages. And, in the numerical range recorded in this specification, the upper limit or lower limit of the numerical range can be replaced by the value shown in the embodiment. And, the upper limit and lower limit recorded separately can be combined arbitrarily. In the mark of the numerical range "A~B", the numerical values A and B at both ends are included in the numerical range as the lower limit and upper limit, respectively. In this specification, for example, the record of "more than 10" refers to "10" and "a numerical value exceeding 10", and this shall prevail in the case of different numerical values. And, for example, the record of "less than 10" refers to "10" and "a numerical value less than 10", and this shall prevail in the case of different numerical values.
[0035] In this specification, "(meth)acrylate" refers to at least one of acrylate and its corresponding methacrylate. The same applies to other similar expressions such as "(meth)acryloyl" and "(meth)acrylic acid". In addition, "A or B" may include either A or B, or both.
[0036] Unless otherwise specified, the materials exemplified below can be used alone or in combination of two or more. In the case where there are multiple substances equivalent to each component in the composition, unless otherwise specified, the content of each component in the composition refers to the total amount of the multiple substances present in the composition.
[0037] [Adhesive film for circuit connection]
[0038] Figure 1 This is a schematic cross-sectional view showing one embodiment of the adhesive film for circuit connection. Figure 1The circuit connection adhesive film 10 shown (hereinafter, sometimes simply referred to as "adhesive film 10") includes a first adhesive layer 1 containing conductive particles 4 and an adhesive component 5 containing a predetermined resin as a thermoplastic resin, and a second adhesive layer 2 provided on the first adhesive layer 1. In the adhesive film 10, there may be a first region formed by the first adhesive film (first adhesive layer 1) and a second region provided adjacent to the first region and formed by the second adhesive film (second adhesive layer 2). That is, the adhesive film 10 may also include a first region containing an adhesive component 5 containing a predetermined resin as a thermoplastic resin and a second region provided adjacent to the first region.
[0039] The adhesive film 10 has the conductive particles 4 dispersed in the first adhesive layer 1. Therefore, the adhesive film 10 may be an adhesive film for circuit connection having anisotropic conductivity (anisotropic conductive adhesive film). The adhesive film 10 may be used to interpose between a first circuit component having a first electrode and a second circuit component having a second electrode, and to perform thermocompression bonding on the first circuit component and the second circuit component to electrically connect the first electrode and the second electrode to each other.
[0040] <First adhesive layer>
[0041] The first adhesive layer 1 contains conductive particles 4 (hereinafter, sometimes referred to as "(A) component") and a thermoplastic resin (hereinafter, sometimes referred to as "(B) component".). The first adhesive layer 1 may further contain a cured product of a photocurable resin component (hereinafter, sometimes referred to as "(C) component") and a thermosetting resin component (hereinafter, sometimes referred to as "(D) component".). The first adhesive layer 1 can be obtained, for example, by irradiating a composition layer formed by a composition containing (A) component, (B) component, (C) component and (D) component with light energy to polymerize the components contained in the (C) component and cure the (C) component. The first adhesive layer 1 may contain an adhesive component 5, wherein the adhesive component 5 contains cured products of the (A) component, the (B) component, the (C) component and the (D) component. The cured product of the (C) component may be a cured product obtained by completely curing the (C) component or a cured product obtained by curing a portion of the (C) component. The component (D) is a component that can flow when the circuit is connected, and may be, for example, an uncured curable resin component.
[0042] (A) Ingredients: Conductive particles
[0043] The (A) component is not particularly limited as long as it is a particle with conductivity, and can be a metal particle composed of a metal such as Au, Ag, Pd, Ni, Cu, solder, etc., a conductive carbon particle composed of conductive carbon, etc. The (A) component can also be a coated conductive particle having a core containing non-conductive glass, ceramics, plastic (polystyrene, etc.) and a coating layer containing the above-mentioned metal or conductive carbon and coating the core. Among these, the (A) component is preferably a metal particle formed by a hot melt metal or a coated conductive particle having a core containing plastic and a coating layer containing a metal or conductive carbon and coating the core. With regard to such coated conductive particles, since the cured product of the thermosetting resin component can be easily deformed by heating or pressurizing, for example, when the opposing electrodes of the semiconductor chip and the substrate are electrically connected to each other, the contact area between the electrode and the (A) component can be increased, thereby further improving the conductivity between the electrodes.
[0044] The component (A) may be an insulating coated conductive particle, wherein the insulating coated conductive particle comprises the above-mentioned metal particle, conductive carbon particle or coated conductive particle and an insulating layer, wherein the insulating layer comprises an insulating material such as a resin and covers the surface of the particle. If the component (A) is an insulating coated conductive particle, even when the content of the component (A) is high, since the insulating layer is provided on the surface of the particle, the occurrence of a short circuit caused by contact between the components (A) can be suppressed, and the insulation between adjacent electrode circuits in the semiconductor chip and the substrate can be improved.
[0045] The maximum particle size of the (A) component needs to be smaller than the minimum spacing between the electrodes (the shortest distance between adjacent electrodes). From the viewpoint of excellent dispersibility and conductivity, the maximum particle size of the (A) component can be greater than 1 μm, greater than 2 μm, or greater than 2.5 μm. From the viewpoint of excellent dispersibility and conductivity, the maximum particle size of the (A) component can be less than 20 μm, less than 10 μm, or less than 5 μm. In this specification, for any 300 (pcs) conductive particles, the particle size is measured by observation using a scanning electron microscope (SEM), and the maximum value obtained is taken as the maximum particle size of the (A) component. In addition, in the case where the (A) component has protrusions, etc., and the (A) component is not spherical, the particle size of the (A) component is the diameter of the circle circumscribed with the conductive particles in the SEM image.
[0046] From the viewpoint of excellent dispersibility and conductivity, the average particle size of component (A) may be 1 μm or more, 2 μm or more, or 2.5 μm or more. From the viewpoint of excellent dispersibility and conductivity, the average particle size of component (A) may be 20 μm or less, 10 μm or less, or 5 μm or less. In this specification, for any 300 (pcs) conductive particles, the particle size is measured by observation using a scanning electron microscope (SEM), and the simple average value of the obtained particle size is taken as the average particle size.
[0047] In the first adhesive layer 1, the component (A) is preferably uniformly dispersed. From the viewpoint of obtaining a stable connection resistance, the particle density of the component (A) in the adhesive film 10 may be 100 particles / mm. 2 Above, 1000 pieces / mm 2 Above, 3000 pieces / mm 2 Above or 5000 pcs / mm 2 From the viewpoint of improving the insulation between adjacent electrodes, the particle density of the component (A) in the adhesive film 10 may be 100,000 particles / mm 2 Below, 70,000 pieces / mm 2 Below, 50000 pieces / mm 2 Below or 30000 pcs / mm 2 the following.
[0048] From the viewpoint of being able to further improve the conductivity, the content of the component (A) may be 1% by mass or more, 5% by mass or more, or 10% by mass or more, based on the total mass of the first adhesive layer. From the viewpoint of easily suppressing short circuits, the content of the component (A) may be 80% by mass or less, 60% by mass or less, or 40% by mass or less, based on the total mass of the first adhesive layer. If the content of the component (A) is within the above range, there is a tendency to significantly exert the effect of the present invention. In addition, the content of the component (A) in the composition or the composition layer (based on the total mass of the composition or the composition layer) may be the same as the above range.
[0049] (B) Component: Thermoplastic resin
[0050] The component (B) contains a resin in which at least a part of the hydroxyl groups in the above-mentioned phenoxy resin is modified with a group represented by formula (1) or formula (1A) (hereinafter, sometimes referred to as "component (B1)"). The component (B1) is not contained in the component (C1) (radical polymerizable compound) described later. In addition to the component (B1), the component (B) may further contain a thermoplastic resin other than the component (B1) (hereinafter, sometimes referred to as "component (B2)").
[0051] Component (B1): a phenoxy resin in which at least a portion of the hydroxyl groups are modified with a group represented by formula (1) or formula (1A)
[0052] A resin in which at least a part of the hydroxyl groups in a phenoxy resin is modified by a group represented by formula (1) (hereinafter, sometimes referred to as "resin (1)") can be referred to as a reaction product of a phenoxy resin and an isocyanate compound having a (meth)acryloyl group. The isocyanate compound having a (meth)acryloyl group is a compound represented by the following formula (2). That is, the group represented by formula (1) is a group derived from the compound represented by formula (2). Resin (1) is a component that can function as a thermoplastic resin.
[0053] By making the adhesive composition contain component (B1) as component (B), it is possible to form an adhesive film for circuit connection that can suppress the localization of conductive particles even when heat and external force are applied. Although the reason for this effect is not completely clear, the inventors speculate that this is because the (meth)acryloyl groups in the group represented by formula (1) are cross-linked between or within molecules by light irradiation (for example, ultraviolet light) or heat, thereby improving the toughness of the film and effectively suppressing the proximity of conductive particles to each other. In addition, this effect tends to be further improved by the fact that component (B) includes components (B1) and (B2).
[0054]
[0055] In formula (1), R 1 represents a hydrogen atom or a methyl group. x represents an integer of 2 to 6, and may be 2 to 5, 2 to 4, or 2 to 3. y represents an integer of 1 to 6, and may be 1 to 5, 1 to 4, 1 to 3, or 1 to 2. * represents a bonding position to the oxygen atom derived from the hydroxyl group.
[0056]
[0057] In formula (2), R 1 , x and y have the same meanings as above.
[0058] The compound represented by formula (2) can be obtained by a known method such as a phosgene method using an amino alcohol having a corresponding ether bond, or a commercially available product can be used. The compound represented by formula (2) can be obtained, for example, by reacting an amino alcohol having an ether bond such as 2-(2-aminoethoxy)ethanol, 2-(2-(2-aminoethoxy)ethoxy)ethanol with an acyl chloride such as (meth)acryloyl chloride, and further reacting with phosgene. Examples of commercially available products include Karenz (registered trademark) MOI (R 1 A compound represented by the formula (2) wherein x is 2 and y is 1, manufactured by SHOWA DENKO KK), Karenz (registered trademark), AOI (R 1A compound represented by the formula (2) wherein x is a hydrogen atom, y is 1, manufactured by SHOWA DENKO KK), Karenz (registered trademark), MOI-EG (R 1 A compound represented by the formula (2) wherein x is methyl, 2 and y is 2, manufactured by SHOWA DENKO KK) or the like.
[0059] Phenoxy resins can be obtained, for example, by reacting a polyphenol compound with a polyepoxy compound. Such phenoxy resins generally have a structure in which an aliphatic hydroxyl group is generated at a bonding portion formed by a reaction between an aromatic hydroxyl group (hydroxyl group) and an epoxy group (for example, a structure derived from the following formula (X)). As such phenoxy resins, resins obtained by reacting bisphenols with diglycidyl etherified bisphenols are easily available and relatively common.
[0060] Examples of the polyphenol compound include bisphenol A and bisphenol F. Examples of the polyepoxy compound include bisphenol A diglycidyl ether and bisphenol F diglycidyl ether.
[0061] The phenoxy resin may be a polyhydroxy polyether (thermoplastic resin) synthesized from bisphenols and epichlorohydrin. Such a phenoxy resin generally has a structure derived from the following formula (X) derived from epichlorohydrin (* indicates a bonding position.), and the hydroxyl group of the phenoxy resin is bonded to a methine carbon atom (C A ) bonding.
[0062]
[0063] Commercially available phenoxy resins can be used. Examples of commercially available phenoxy resins include FX-293, YP-70, ZX1356-2, FX-310, and TOPR-300 (all manufactured by NIPPON STEEL Chemical & Material Co., Ltd.), PKHA, PKHB, PKHC, PKHH, PKHJ, PKFE, and PKHP-200 (all manufactured by Huntsman International LLC.), jER1256, jER4250, and jER4275 (all manufactured by Mitsubishi Chemical Corporation), and H360 and EXA-192 (all manufactured by DIC Corporation).
[0064] The modification rate of the group represented by formula (1) relative to the hydroxyl group of the phenoxy resin can be 0.5 to 50%. If the modification rate is 0.5% or more, there is a tendency to fully suppress the localization of the conductive particles. If the modification rate is 50% or less, there is a tendency for the connection resistance of the circuit connection portion to become better. The modification rate can be 1.0% or more, 3.0% or more, or 5.0% or more, or 40% or less, 30% or less, 20% or less, 15% or less, or 10% or less.
[0065] Here, the modification ratio of the group represented by the formula (1) to the hydroxyl group of the phenoxy resin can be determined, for example, by modifying the resin modified with the group represented by the formula (1). 1 The HNMR measurement was performed and the peak integral value in the obtained spectrum was calculated. The resin modified with the group represented by the formula (1) has a structure derived from the following formula (Y) in addition to the structure derived from the above formula (X) (* indicates the bonding position). Among the structures derived from the formula (X), the structure attributed to the carbon atom of the methine (C A ) bonded hydrogen atoms (H A ) is usually observed at δ4.2 to 4.4 (based on the methyl group of tetramethylsilane (TMS)). On the other hand, in the structure derived from formula (Y), the chemical shift value attributed to the carbon atom of the methine (C B ) bonded hydrogen atoms (H B ) (based on the methyl group of tetramethylsilane (TMS)) than that attributed to H A The chemical shift value of is shifted to the lower magnetic field and is usually observed at δ5.2 to 6.0. Therefore, by finding the chemical shift value attributable to hydrogen atoms (H B ) relative to the peaks attributable to hydrogen atoms (H A ) and the integral value of the peaks attributed to hydrogen atoms (H B ) is the ratio (percentage) of the total integrated value of the peak (H B The integral value of H A The integral value of +H B The modification rate can be obtained by calculating the integral value of (integral value) × 100 (%). Furthermore, by plotting the relationship between the amount of the compound represented by formula (2) added when the phenoxy resin and the compound represented by formula (2) are reacted and the modification rate, a calibration curve can be prepared, and the modification rate can be derived from the amount of the compound represented by formula (2) added.
[0066]
[0067] The resin (1) can be obtained by reacting a phenoxy resin with a compound represented by the formula (2) in an organic solvent in the presence of a catalyst as required.
[0068] The amount of the compound represented by formula (2) added can be arbitrarily set so that the modification rate of the group represented by formula (1) with respect to the hydroxyl group of the phenoxy resin becomes a predetermined value. The amount of the compound represented by formula (2) added can be 0.5 to 50 mol% relative to the molar mass of all hydroxyl groups of the phenoxy resin. The amount of the compound represented by formula (2) added can be 1.0 mol% or more, 3.0 mol% or more, or 5.0 mol% or less, or 40 mol% or less, 30 mol% or less, 20 mol% or less, 15 mol% or less, or 10 mol% or less, relative to the molar mass of all hydroxyl groups of the phenoxy resin.
[0069] The organic solvent can be used without particular limitation as long as it is a solvent capable of dissolving the phenoxy resin and the compound represented by formula (2). Examples of the organic solvent include aromatic hydrocarbons such as toluene, xylene, mesitylene, cumene, and p-cymene; aliphatic hydrocarbons such as hexane and heptane; cycloalkanes such as methylcyclohexane; cyclic ethers such as tetrahydrofuran and 1,4-dioxane; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, and 4-hydroxy-4-methyl-2-pentanone; esters such as methyl acetate, ethyl acetate, butyl acetate, methyl lactate, ethyl lactate, and γ-butyrolactone; carbonates such as ethylene carbonate and propylene carbonate; amides such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone (NMP); and the like.
[0070] The catalyst may be a carbamate catalyst. Examples of the catalyst include tin catalysts such as dibutyltin dilaurate, dibutyltin dichloride, dibutyltin oxide, dibutyltin dibromide, dibutyltin dimaleate, and dioctyltin dilaurate; amine catalysts such as triethylamine, triethylenediamine (TEDA), 1,8-diazabicyclo[5.4.0]undecene-7 (DBU), 1,5-diazabicyclo[4.3.0]nonene-5 (DBN), and 1-isobutyl-2-methylimidazole (IBM); zirconium catalysts such as n-propyl zirconate, n-butyl zirconate, tetraacetylacetonate zirconium, monoacetylacetonate zirconium, and ethyl acetoacetate zirconium. The content of the catalyst may be 0.01 to 1% by mass relative to the total mass of the compound represented by formula (2).
[0071] The reaction temperature of the phenoxy resin and the compound represented by formula (2) may be, for example, 0 to 200° C., 20 to 150° C., or 40 to 100° C. The reaction temperature may be maintained for, for example, 0.1 to 12 hours, or 8 hours or less, 6 hours or less, or 4 hours or less.
[0072] In the first adhesive layer 1, the (meth)acryloyl group of the group represented by the formula (1) in the resin (1) can react (radical polymerize) with the (meth)acryloyl group of the group represented by other formula (1) in the resin (1) or the radical polymerizable group of the component (C1) described later, thereby forming a bond between the carbon atom of the (meth)acryloyl group of the group represented by the formula (1) in the resin (1) and the carbon atom of the other radical polymerizable group (the (meth)acryloyl group of the group represented by other formula (1) in the resin (1), the radical polymerizable group of the component (C1) described later, etc.). That is, a part or all of the group represented by the formula (1) in the resin (1) can be converted into the group represented by the formula (1A).
[0073]
[0074] In formula (1A), R 1 , x, y and * have the same meanings as above. *1 and *2 represent the bonding positions to the carbon atoms of other radical polymerizable groups.
[0075] The content of component (B1) may be 20-100 mass %, 30-100 mass %, 40-100 mass %, 50-100 mass %, 60-100 mass %, 70-100 mass % or 80-100 mass % based on the total mass of component (B).
[0076] Component (B2): Thermoplastic resin other than component (B1)
[0077] Examples of the component (B2) include phenoxy resins, polyester resins, polyamide resins, polyurethane resins, polyester polyurethane resins, and acrylic rubbers that are not modified with a group represented by formula (1) or formula (1A). Among these, the component (B2) may be, for example, a phenoxy resin that is not modified with a group represented by formula (1) or formula (1A).
[0078] The content of the component (B2) may be, for example, 0 to 80 mass %, 0 to 70 mass %, 0 to 60 mass %, 0 to 50 mass %, 0 to 40 mass %, 0 to 30 mass % or 0 to 20 mass % based on the total mass of the component (B).
[0079] The content of the component (B) may be 1% by mass or more, 5% by mass or more, or 10% by mass or more, or 50% by mass or less, 40% by mass or less, or 30% by mass or less, based on the total mass of the adhesive composition. In addition, the content of the component (B) in the adhesive layer (based on the total mass of the adhesive layer) may be the same as the above range.
[0080] Component (C): Photocurable resin component
[0081] The first adhesive layer 1 may further contain a cured product of component (C). By curing component (C), it is possible to suppress the fluidity of the conductive particles during circuit connection while suppressing the reduction in the removability of the resin. Regarding component (C), there is no particular limitation as long as it is a resin component that is cured by light irradiation, but in the case where component (D) is a resin component with cation curing properties, it may be a resin component with free radical curing properties from the viewpoint of better connection resistance. Component (C), for example, may include a free radical polymerizable compound (hereinafter, sometimes referred to as "component (C1)") and a photoradical polymerization initiator (hereinafter, sometimes referred to as "component (C2)"). Component (C) may be a component composed of component (C1) and component (C2).
[0082] Component (C1): Radical polymerizable compound
[0083] The component (C1) is a compound that polymerizes or crosslinks by utilizing free radicals generated by irradiating the component (C2) with light (e.g., ultraviolet light). The component (C1) may be a monomer or a polymer (or oligomer) obtained by polymerizing one or more monomers.
[0084] The component (C1) is a compound having a radical polymerizable group that reacts by free radicals. As the radical polymerizable group, for example, (meth)acryloyl, vinyl, allyl, styryl, alkenyl, alkenylene, maleimide, etc. can be cited. From the viewpoint that the desired melt viscosity is easily obtained after polymerization, the effect of reducing the connection resistance is further improved, and the connection reliability is more excellent, the number of radical polymerizable groups (functional groups) possessed by the component (C1) can be more than 2, and from the viewpoint of suppressing the curing shrinkage during polymerization, it can be less than 10. In addition, in order to maintain the balance between the crosslinking density and the curing shrinkage, in addition to the compounds whose number of radical polymerizable groups is within the above range, compounds whose number of radical polymerizable groups is outside the above range can also be used.
[0085] From the viewpoint of suppressing the flow of the conductive particles, for example, the component (C1) may contain a polyfunctional (difunctional or higher) (meth)acrylate. The polyfunctional (difunctional or higher) (meth)acrylate may be a difunctional (meth)acrylate, and the difunctional (meth)acrylate may be a difunctional aromatic (meth)acrylate.
[0086] Examples of the polyfunctional (meth)acrylate include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetrapropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, ethoxylated polypropylene glycol di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, 1,4-butylene glycol di(meth)acrylate, and neopentyl glycol di(meth)acrylate. , 3-methyl-1,5-pentanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 2-butyl-2-ethyl-1,3-propanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, glycerol di(meth)acrylate, tricyclodecane dimethanol (meth)acrylate, ethoxylated 2-methyl-1,3-propanediol di(meth)acrylate and other aliphatic (meth)acrylates; ethoxylated bisphenol A di(meth)acrylate, propoxylated bisphenol A di(meth)acrylate, ethoxylated propoxylated bisphenol A di(meth)acrylate, Ethoxylated bisphenol F di(meth)acrylate, propoxylated bisphenol F di(meth)acrylate, ethoxylated propoxylated bisphenol F di(meth)acrylate, ethoxylated fluorene di(meth)acrylate, propoxylated fluorene di(meth)acrylate, ethoxylated propoxylated fluorene di(meth)acrylate and other aromatic (meth)acrylates, trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, ethoxylated propoxylated trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, ethoxylated pentaerythritol tri(meth)acrylate Aliphatic (meth)acrylates such as (meth)acrylate, propoxylated pentaerythritol tri(meth)acrylate, ethoxylated propoxylated pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, propoxylated pentaerythritol tetra(meth)acrylate, ethoxylated propoxylated pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetraacrylate, and dipentaerythritol hexa(meth)acrylate; aromatic epoxy (meth)acrylates such as bisphenol type epoxy (meth)acrylate, phenol novolac type epoxy (meth)acrylate, and cresol novolac type epoxy (meth)acrylate, etc.
[0087] From the viewpoint of achieving both the effect of reducing connection resistance and suppressing particle flow, the content of the polyfunctional (bifunctional or higher) (meth)acrylate may be, for example, 40 to 100 mass %, 50 to 100 mass %, or 60 to 100 mass % based on the total mass of the component (C1).
[0088] The component (C1) may further contain a monofunctional (meth)acrylate in addition to a polyfunctional (two or more functional) (meth)acrylate. Examples of the monofunctional (meth)acrylate include (meth)acrylic acid; methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, butoxyethyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, heptyl (meth)acrylate, octylheptyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate; aliphatic (meth)acrylates such as ester, 2-hydroxypropyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, ethoxypolyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, ethoxypolypropylene glycol (meth)acrylate, mono(2-(meth)acryloyloxyethyl)succinate; benzyl (meth)acrylate, phenyl (meth)acrylate, o-biphenyl (meth)acrylate, 1(meth)acrylate -naphthyl (meth)acrylate, 2-naphthyl (meth)acrylate, phenoxyethyl (meth)acrylate, p-cumylphenoxyethyl (meth)acrylate, o-phenylphenoxyethyl (meth)acrylate, 1-naphthyloxyethyl (meth)acrylate, 2-naphthyloxyethyl (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, nonylphenoxypolyethylene glycol (meth)acrylate, phenoxypolypropylene glycol (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-hydroxy-3-(o-phenylphenoxy)propyl Aromatic (meth)acrylates such as hydroxy-3-(1-naphthyloxy)propyl (meth)acrylate, 2-hydroxy-3-(2-naphthyloxy)propyl (meth)acrylate; (meth)acrylates having an epoxy group such as glycidyl (meth)acrylate, (meth)acrylates having an alicyclic epoxy group such as 3,4-epoxycyclohexylmethyl (meth)acrylate, (meth)acrylates having an oxetane group such as (3-ethyloxetan-3-yl)methyl (meth)acrylate, and the like.
[0089] The content of the monofunctional (meth)acrylate may be, for example, 0 to 60% by mass, 0 to 50% by mass, or 0 to 40% by mass based on the total mass of the component (C1).
[0090] The cured product of component (C) may have, for example, a polymerizable group that reacts other than free radicals. The polymerizable group that reacts other than free radicals may be, for example, a cationic polymerizable group that reacts by cations. Examples of cationic polymerizable groups include epoxy groups such as glycidyl, alicyclic epoxy groups such as epoxycyclohexylmethyl, and oxetane groups such as ethyloxetanemethyl. Regarding polymerizable groups that react other than free radicals, for example, (meth)acrylates having polymerizable groups that react other than free radicals, such as (meth)acrylates having epoxy groups, (meth)acrylates having alicyclic epoxy groups, and (meth)acrylates having oxetane groups, can be introduced into the cured product of component (C) by using, as component (C1), (meth)acrylates having polymerizable groups that react other than free radicals. From the viewpoint of improving reliability, the mass ratio of the (meth)acrylate having a polymerizable group that reacts other than free radicals to the total mass of the component (C1) (mass (charge amount) of the (meth)acrylate having a polymerizable group that reacts other than free radicals / total mass (charge amount) of the component (C1)) can be, for example, 0 to 0.7, 0 to 0.5, or 0 to 0.3.
[0091] The component (C1) may contain other radical polymerizable compounds in addition to polyfunctional (two or more functional) and monofunctional (meth)acrylates. Examples of other radical polymerizable compounds include maleimide compounds, vinyl ether compounds, allyl compounds, styrene derivatives, acrylamide derivatives, and nadic imide derivatives. The content of other radical polymerizable compounds may be, for example, 0 to 40% by mass based on the total mass of the component (C1).
[0092] Component (C2): Photoradical polymerization initiator
[0093] The component (C2) is a photopolymerization initiator that generates radicals when irradiated with light having a wavelength in the range of 150 to 750 nm, light having a wavelength in the range of 254 to 405 nm, or light having a wavelength in the range of 365 nm (eg, ultraviolet light).
[0094] The component (C2) is photodecomposed to generate free radicals. That is, the component (C2) is a compound that generates free radicals by applying light energy from the outside. The component (C2) may be a compound having structures such as an oxime ester structure, a bisimidazole structure, an acridine structure, an α-aminoalkylphenone structure, an aminobenzophenone structure, an N-phenylglycine structure, an acylphosphine oxide structure, a benzyldimethylketal structure, and an α-hydroxyalkylphenone structure. From the viewpoint of easily obtaining the desired melt viscosity and having a better effect of reducing the connection resistance, the component (C2) may also be a compound having at least one structure selected from the group consisting of an oxime ester structure, an α-aminoalkylphenone structure, and an acylphosphine oxide structure.
[0095] Specific examples of the compound having an oxime ester structure include 1-phenyl-1,2-butanedione-2-(o-methoxycarbonyl)oxime, 1-phenyl-1,2-propanedione-2-(o-methoxycarbonyl)oxime, 1-phenyl-1,2-propanedione-2-(o-ethoxycarbonyl)oxime, 1-phenyl-1,2-propanedione-2-o-benzoyloxime, 1,3-diphenylpropanetrione-2-(o-ethoxycarbonyl)oxime, 1-phenyl-3-ethoxypropanetrione-2-(o-benzoyl)oxime, 1,2-octanedione, 1-[4-(phenylthio)phenyl-, 2-(o-benzoyloxime)], ethyl ketone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(o-acetyloxime), and the like.
[0096] Specific examples of the compound having an α-aminoalkylphenone structure include 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropane-1-one and 2-benzyl-2-dimethylamino-1-morpholinophenyl)-butanone-1-one.
[0097] Specific examples of the compound having an acylphosphine oxide structure include bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
[0098] From the viewpoint of suppressing the flow of the conductive particles, the content of the component (C2) may be, for example, 0.1 to 10 parts by mass, 0.3 to 7 parts by mass, or 0.5 to 5 parts by mass based on 100 parts by mass of the component (C1).
[0099] From the viewpoint of suppressing the flow of conductive particles, the content of the cured product of the component (C) (the total of the component (C1) and the component (C2)) may be 1% by mass or more, 5% by mass or more, or 10% by mass or more, based on the total mass of the first adhesive layer. From the viewpoint of the effect of reducing the connection resistance, the content of the cured product of the component (C) may be 50% by mass or less, 40% by mass or less, or 30% by mass or less, based on the total mass of the first adhesive layer. If the content of the cured product of the component (C) is within the above range, there is a tendency to significantly exert the effect of the present invention. In addition, the content of the component (C) in the composition or the composition layer (based on the total mass of the composition or the composition layer) may be the same as the above range.
[0100] (D) Component: Thermosetting resin component
[0101] The first adhesive layer 1 may further contain a component (D). The component (D) is not particularly limited as long as it is a resin component that is cured by heat, but when the component (C) is a resin component having free radical curability, the component (D) may be a resin component having cation curability from the viewpoint of better connection resistance. The component (D) may include, for example, a cationic polymerizable compound (hereinafter, sometimes referred to as "component (D1)") and a thermal cationic polymerization initiator (hereinafter, sometimes referred to as "component (D2)"). The component (D) may be a component composed of components (D1) and (D2). In addition, the first thermosetting resin component, the second thermosetting resin component, and the third thermosetting resin component refer to the thermosetting resin components contained in the first adhesive layer, the second adhesive layer, and the third adhesive layer, respectively, and the types and contents of the components (for example, component (D1), component (D2), etc.) contained in the first thermosetting resin component, the second thermosetting resin component, and the third thermosetting resin component may be the same as or different from each other.
[0102] Component (D1): Cationic polymerizable compound
[0103] The component (D1) is a compound that is polymerized or cross-linked using a substance (acid, etc.) generated by heating the component (D2). In addition, the component (D1) refers to a compound that does not have a free radical polymerizable group that reacts by free radicals, and the component (D1) is not included in the component (C1). From the viewpoint of further improving the effect of reducing the connection resistance and improving the connection reliability, the component (D1) may be, for example, at least one selected from the group consisting of an oxetane compound and an alicyclic epoxy compound. From the viewpoint of easily obtaining the desired melt viscosity, the component (D1) preferably includes both an oxetane compound and an alicyclic epoxy compound.
[0104] The oxetane compound as the component (D1) can be used without particular limitation as long as it has an oxetane group and does not have a radical polymerizable group. Examples of commercially available oxetane compounds include ETERNACOLL OXBP (trade name, 4,4'-bis[(3-ethyl-3-oxetane)methoxymethyl]biphenyl, manufactured by UBE Corporation), OXSQ, OXT-121, OXT-221, OXT-101, and OXT-212 (trade names, manufactured by TOAGOSEI CO., LTD.).
[0105] The alicyclic epoxy compound as the component (D1) can be used without particular limitation as long as it is a compound having an alicyclic epoxy group (e.g., an epoxycyclohexyl group) and having no radical polymerizable group. Examples of commercially available alicyclic epoxy compounds include EHPE3150, EHPE3150CE, CELLOXIDE8010, CELLOXIDE2021P, and CELLOXIDE2081 (trade names, manufactured by Daicel Corporation).
[0106] Component (D2): Thermal cationic polymerization initiator
[0107] The component (D2) is a thermal polymerization initiator that generates an acid or the like by heating to initiate polymerization. The component (D2) may be a salt compound composed of a cation and an anion. For example, the component (D2) may include BF4 - BR4 - (R represents a phenyl group substituted with two or more fluorine atoms or two or more trifluoromethyl groups.), PF6 - 、SbF6 - 、AsF6 - Onium salts such as sulfonium salts, phosphonium salts, ammonium salts, diazonium salts, iodonium salts, anilinium salts and the like of anions.
[0108] From the viewpoint of storage stability, the component (D2) may be, for example, an anion containing boron as a constituent element, that is, BF4 - or BR4 - (R represents a phenyl group substituted with two or more fluorine atoms or two or more trifluoromethyl groups.) The anion containing boron as a constituent element may be BR4 - , more specifically, it may be tetrakis(pentafluorophenyl)borate.
[0109] From the viewpoint of having resistance to substances that may inhibit the curing of cationic curing, the onium salt as the component (D2) may be, for example, an anilinium salt. Examples of the anilinium salt compound include N,N-dimethylanilinium salts, N,N-diethylanilinium salts and other N,N-dialkylanilinium salts.
[0110] The component (D2) may be an anilinium salt having an anion containing boron as a constituent element. Examples of commercially available products of such salt compounds include CXC-1821 (trade name, manufactured by King Industries, Inc.).
[0111] From the viewpoint of ensuring the formability and curability of the adhesive film for forming the first adhesive layer, the content of the component (D2) may be, for example, 0.1 to 20 parts by mass, 1 to 18 parts by mass, 3 to 15 parts by mass, or 5 to 12 parts by mass based on 100 parts by mass of the component (D1).
[0112] From the viewpoint of ensuring the curability of the adhesive film used to form the first adhesive layer, the content of the (D) component may be 5% by mass or more, 10% by mass or more, 15% by mass or more, or 20% by mass or more, based on the total mass of the first adhesive layer. From the viewpoint of ensuring the formability of the adhesive film used to form the first adhesive layer, the content of the (D) component may be 70% by mass or less, 60% by mass or less, 50% by mass or less, or 40% by mass or less, based on the total mass of the first adhesive layer. If the content of the (D) component is within the above range, there is a tendency to significantly exert the effect of the present invention. In addition, the content of the (D) component in the composition or the composition layer (based on the total mass of the composition or the composition layer) may be the same as the above range.
[0113] Other Ingredients
[0114] The first adhesive layer 1 may further contain other components in addition to the (A) component, the (B) component, the (C) component (cured product of the (C) component), and the (D) component. Examples of other components include coupling agents (hereinafter sometimes referred to as "(E) components"), fillers (hereinafter sometimes referred to as "(F) components"), and the like.
[0115] As the (E) component, for example, silane coupling agents having organic functional groups such as (meth)acryloyl, mercapto, amino, imidazole, and epoxy groups, silane compounds such as tetraalkoxysilane, tetraalkoxy titanate derivatives, and polydialkyl titanate derivatives can be cited. By containing the (E) component in the first adhesive layer 1, the adhesion can be further improved. The (E) component can be, for example, a silane coupling agent. The content of the (E) component can be 0.1 to 10% by mass based on the total mass of the first adhesive layer. In addition, the content of the (E) component in the composition or the composition layer (based on the total mass of the composition or the composition layer) can be the same as the above range.
[0116] As the (F) component, for example, non-conductive fillers (for example, non-conductive particles) can be mentioned. The (F) component can also be any of an inorganic filler and an organic filler. As an inorganic filler, for example, metal oxide particles such as silica particles, alumina particles, silica-alumina particles, titanium dioxide particles, and zirconium dioxide particles; inorganic particles such as metal nitride particles can be mentioned. As an organic filler, for example, organic particles such as silicone particles, methacrylate / butadiene / styrene particles, acrylic / silicone particles, polyamide particles, and polyimide particles can be mentioned. The (F) component can be, for example, silica particles. Based on the total mass of the first adhesive layer, the content of the (F) component can be 0.1 to 10% by mass. In addition, the content of the (F) component in the composition or the composition layer (based on the total mass of the composition or the composition layer) can be the same as the above range.
[0117] Other additives
[0118] The first adhesive layer 1 may further contain other additives such as a softener, an accelerator, an anti-degradation agent, a colorant, a flame retardant, a thixotropic agent, etc. The content of other additives may be, for example, 0.1 to 10% by mass based on the total mass of the first adhesive layer. In addition, the content of other additives in the composition or the composition layer (based on the total mass of the composition or the composition layer) may be the same as the above range.
[0119] The thickness d1 of the first adhesive layer 1 may be 5 μm or less, for example, 4.5 μm or less, 4 μm or less, 3.5 μm or less, 3 μm or less, or 2.5 μm or less. By making the thickness d1 of the first adhesive layer 1 5 μm or less, the fluidity of the conductive particles during circuit connection can be further suppressed. The thickness d1 of the first adhesive layer 1 may be, for example, 0.1 μm or more or 0.7 μm or more. In addition, Figure 1As shown in FIG. 1 , when a portion of the conductive particles 4 are exposed from the surface of the first adhesive layer 1 (for example, protruding toward the second adhesive layer 2 side), the distance (in the range of 0 to 100°) from the surface 2a of the first adhesive layer 1 on the side opposite to the second adhesive layer 2 side to the boundary S between the first adhesive layer 1 and the second adhesive layer 2 located at the separation portion between the adjacent conductive particles 4 and 4 is Figure 1 The distance d1 in FIG. 1 is the thickness of the first adhesive layer 1, and the exposed portion of the conductive particles 4 is not included in the thickness of the first adhesive layer 1. The length of the exposed portion of the conductive particles 4 may be, for example, 0.1 μm or more, or 5 μm or less.
[0120] The ratio of the thickness of the first adhesive layer 1 to the average particle size of the component (A) (conductive particles 4) (the thickness of the first adhesive layer 1 / the average particle size of the component (A) (conductive particles 4)) may be 0.50 or more, for example, 0.55 or more or 0.60 or more. When the ratio is 0.50 or more, the resin component between the opposing circuits is reduced, and the increase in the connection resistance between the opposing circuits can be suppressed. The ratio may be, for example, 2.00 or less, 1.50 or less, 1.20 or less, 1.00 or less, or 0.80 or less.
[0121] <Second adhesive layer>
[0122] The second adhesive layer 2 may contain a component (D). Since the components (D1) and (D2) used in the component (D) (i.e., the second thermosetting resin component) in the second adhesive layer 2 are the same as the components (D1) and (D2) used in the component (D) (i.e., the first thermosetting resin component) in the first adhesive layer 1, detailed description thereof is omitted here. The second thermosetting resin component may be the same as or different from the first thermosetting resin component.
[0123] From the viewpoint of maintaining reliability, the content of the component (D) (the total of the component (D1) and the component (D2)) may be 5% by mass or more, 10% by mass or more, 15% by mass or more, or 20% by mass or more, based on the total mass of the second adhesive layer. From the viewpoint of preventing resin seepage problems in the reel as one mode of supply, the content of the component (D) (the total of the component (D1) and the component (D2)) may be 70% by mass or less, 60% by mass or less, 50% by mass or less, or 40% by mass or less, based on the total mass of the second adhesive layer.
[0124] The second adhesive layer 2 may further contain the component (B) in the first adhesive layer 1. The component (B) may not contain the component (B1) but may consist only of the component (B2). That is, the second adhesive layer 2 may further contain the component (B2) as the component (B). The content of the component (B) may be 1% by mass or more, 5% by mass or more, or 10% by mass or more, or may be 80% by mass or less, 60% by mass or less, or 40% by mass or less, based on the total mass of the second adhesive layer.
[0125] The second adhesive layer 2 may further contain other components and other additives in the first adhesive layer 1. Preferred aspects of the other components and other additives are the same as those of the first adhesive layer 1.
[0126] The content of the component (E) may be 0.1 to 10% by mass based on the total mass of the second adhesive layer.
[0127] The content of the component (F) may be 1 mass % or more, 10 mass % or more, or 30 mass % or less, or 90 mass % or less, 70 mass % or less, or 50 mass % or less based on the total mass of the second adhesive layer.
[0128] The content of other additives may be, for example, 0.1 to 10% by mass based on the total mass of the second adhesive layer.
[0129] The thickness d2 of the second adhesive layer 2 can be appropriately set according to the height of the electrodes of the bonded circuit components, etc. From the viewpoint of being able to fully fill the space between the electrodes to seal the electrodes and obtain better connection reliability, the thickness d2 of the second adhesive layer 2 can be 5 μm or more, or 7 μm or less, or 15 μm or less, or 11 μm or less. In addition, when a portion of the conductive particles 4 are exposed from the surface of the first adhesive layer 1 (for example, protruding toward the second adhesive layer 2 side), the distance from the surface 3a of the second adhesive layer 2 on the side opposite to the first adhesive layer 1 to the boundary S between the first adhesive layer 1 and the second adhesive layer 2 located at the separation portion of the adjacent conductive particles 4, 4 (at Figure 1 The distance represented by d2 in the figure is the thickness of the second adhesive layer 2.
[0130] The thickness of the adhesive film 10 (the total thickness of all layers constituting the adhesive film 10, Figure 1 In the embodiment, the total thickness d1 of the first adhesive layer 1 and the thickness d2 of the second adhesive layer 2 (ie, the total thickness d2) may be, for example, 5 μm or more or 8 μm or more, or 30 μm or less or 20 μm or less.
[0131] In the adhesive film 10, the conductive particles 4 are dispersed in the first adhesive layer 1. Therefore, the adhesive film 10 is an anisotropic conductive adhesive film having anisotropic conductivity. The adhesive film 10 is used to be interposed between a first circuit component having a first electrode and a second circuit component having a second electrode, and the first circuit component and the second circuit component are thermally pressed to electrically connect the first electrode and the second electrode to each other.
[0132] According to the adhesive film 10 , by containing the component (B1) as the component (B), it is possible to form an adhesive film for circuit connection that can suppress localization of the conductive particles even when heat and external force are applied.
[0133] As mentioned above, although the adhesive film of this embodiment was demonstrated, this invention is not limited to the said embodiment.
[0134] The adhesive film may be composed of two layers, the first adhesive layer and the second adhesive layer, or may be composed of three or more layers including the first adhesive layer and the second adhesive layer. The adhesive film may further include a third adhesive layer, which is disposed on the side of the first adhesive layer opposite to the second adhesive layer and contains a (third) thermosetting resin component. In the adhesive film, there may be a first region and a second region, the first region being a region formed by the first adhesive film (first adhesive layer), and the third region being a region disposed adjacent to the first region and formed by the third adhesive film (third adhesive layer). The adhesive film may further include a third region, which is disposed adjacent to the side of the first region opposite to the second region and contains a (third) thermosetting resin component.
[0135] The third adhesive layer may contain component (D). Since the components (D1) and (D2) used in the component (D) (i.e., the third thermosetting resin component) in the third adhesive layer are the same as the components (D1) and (D2) used in the component (D) (i.e., the first thermosetting resin component) in the first adhesive layer 1, detailed description thereof is omitted here. The third thermosetting resin component may be the same as or different from the first thermosetting resin component. The third thermosetting resin component may be the same as or different from the second thermosetting resin component.
[0136] From the viewpoint of imparting good transferability and peeling resistance, the content of the component (D) (the total of the component (D1) and the component (D2)) may be 5% by mass or more, 10% by mass or more, 15% by mass or more, or 20% by mass or more, based on the total mass of the third adhesive layer. From the viewpoint of imparting good half-cutting properties and blocking resistance (suppressing resin exudation of the reel), the content of the component (D) (the total of the component (D1) and the component (D2)) may be 70% by mass or less, 60% by mass or less, 50% by mass or less, or 40% by mass or less, based on the total mass of the third adhesive layer.
[0137] The third adhesive layer may further contain the component (B) in the first adhesive layer 1. The component (B) may not contain the component (B1) but may consist only of the component (B2). That is, the third adhesive layer may further contain the component (B2) as the component (B). The content of the component (B) may be 10% by mass or more, 20% by mass or more, or 30% by mass or more, or 80% by mass or less, 70% by mass or less, or 60% by mass or less, based on the total mass of the second adhesive layer.
[0138] The third adhesive layer may further contain other components and other additives in the first adhesive layer 1. Preferred aspects of the other components and other additives are the same as those of the first adhesive layer 1.
[0139] The content of the component (E) may be 0.1 to 10% by mass based on the total mass of the third adhesive layer.
[0140] The content of the component (F) may be 1 mass % or more, 5 mass % or more, or 10 mass % or less, or 50 mass % or less, 40 mass % or less, or 30 mass % or less, based on the total mass of the third adhesive layer.
[0141] The content of other additives may be, for example, 0.1 to 10% by mass based on the total mass of the third adhesive layer.
[0142] The thickness of the third adhesive layer can be appropriately set according to the height of the electrodes of the bonded circuit component, etc. From the viewpoint of being able to sufficiently fill the space between the electrodes to seal the electrodes and obtain better connection reliability, the thickness of the third adhesive layer can be 0.2 μm or more, or 3 μm or less.
[0143] Furthermore, the circuit-connecting adhesive film of the above-described embodiment is an anisotropically conductive adhesive film having anisotropic conductivity, but the circuit-connecting adhesive film may be a conductive adhesive film not having anisotropic conductivity.
[0144] [Method for producing adhesive film for circuit connection]
[0145] A method for producing an adhesive film for circuit connection according to one embodiment may include, for example, the following steps: irradiating a composition layer formed of a composition containing component (A), component (B) containing component (B1) (resin (resin (1) in which at least a portion of the hydroxyl groups in a phenoxy resin are modified with a group represented by formula (1)), component (C) and component (D) (first thermosetting resin component) with light to form a first adhesive layer (first step); and laminating a second adhesive layer containing component (D) (second thermosetting resin component) on the first adhesive layer (second step). The production method may further include laminating a third adhesive layer containing component (D) (third thermosetting resin component) on the layer on the opposite side of the first adhesive layer to the second adhesive layer (third step).
[0146] In the first step, for example, first, a composition containing component (A), component (B) containing component (B1) (resin (1)), component (C) and component (D), and other components and other additives added as needed are stirred, mixed, kneaded, etc. in an organic solvent to dissolve or disperse them, thereby preparing a varnish composition. Then, the varnish composition is applied to a substrate subjected to a demolding treatment using a knife coater, a roll coater, an applicator, a comma coater, a die coater, etc., and the organic solvent is volatilized by heating to form a composition layer formed by the composition on the substrate. At this time, the thickness of the first adhesive layer (first adhesive film) finally obtained can be adjusted by adjusting the coating amount of the varnish composition. Next, the composition layer formed by the composition is irradiated with light to cure the component (C) in the composition layer, thereby forming the first adhesive layer on the substrate. In this case, part or all of the groups represented by formula (1) in the resin (1) as the component (B1) may be converted into groups represented by formula (1A). The first adhesive layer can be referred to as a first adhesive film.
[0147] The organic solvent used in the preparation of the varnish composition is not particularly limited as long as it has the property of being able to uniformly dissolve or disperse each component. As such an organic solvent, for example, toluene, acetone, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, propyl acetate, butyl acetate, etc. can be cited. These organic solvents can be used alone or in combination of two or more. The stirring, mixing or kneading when preparing the varnish composition can be carried out, for example, using a stirrer, a mortar machine, a three-roller, a ball mill, a bead mill, a homogenizing disperser, etc.
[0148] The substrate is not particularly limited as long as it has heat resistance that can withstand the heating conditions for volatilizing the organic solvent. As such a substrate, for example, a substrate (e.g., a film) formed of stretched polypropylene (OPP), polyethylene terephthalate (PET), polyethylene naphthalate, polyethylene isophthalate, polybutylene terephthalate, polyolefin, polyacetate, polycarbonate, polyphenylene sulfide, polyamide, polyimide, cellulose, ethylene-vinyl acetate copolymer, polyvinyl chloride, polyvinylidene chloride, synthetic rubber, liquid crystal polymer, etc. can be used.
[0149] The heating conditions for volatilizing the organic solvent from the varnish composition applied on the substrate can be appropriately set according to the organic solvent used, etc. The heating conditions may be, for example, heating at 40 to 120° C. for 0.1 to 10 minutes.
[0150] In the light irradiation in the curing process, it is preferred to use irradiation light having a wavelength in the range of 150 to 750 nm (e.g., ultraviolet light). Regarding the light irradiation, for example, a low-pressure mercury lamp, a medium-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a xenon lamp, a metal halide lamp, an LED light source, etc. can be used. The cumulative light amount of the light irradiation can be appropriately set, for example, it can be 500 to 3000 mJ / cm 2 .
[0151] The second step is a step of laminating the second adhesive layer on the first adhesive layer. In the second step, for example, first, the second adhesive layer is formed on the substrate in the same manner as the first step, using the component (D) and other components and other additives added as needed, and light irradiation is not performed, thereby obtaining a second adhesive film. Then, by laminating the first adhesive film and the second adhesive film, the second adhesive layer can be laminated on the first adhesive layer. In addition, in the second step, for example, by applying a varnish composition obtained by using the component (D) and other components and other additives added as needed on the first adhesive layer and volatilizing the organic solvent, the second adhesive layer can also be laminated on the first adhesive layer.
[0152] Examples of the method for bonding the first adhesive film and the second adhesive film include heat pressing, roll lamination, vacuum lamination, etc. The lamination can be performed at a temperature of 0 to 80°C, for example.
[0153] The third step is a step of laminating a third adhesive layer on the layer on the side opposite to the second adhesive layer of the first adhesive layer. In the third step, for example, first, in the same manner as in the second step, a third adhesive layer is formed on a substrate to obtain a third adhesive film. Next, by laminating the third adhesive film on the side opposite to the second adhesive film of the first adhesive film, the third adhesive layer can be laminated on the layer on the side opposite to the second adhesive layer of the first adhesive layer. In addition, in the third step, for example, by applying a varnish composition on the layer on the side opposite to the second adhesive layer of the first adhesive layer and volatilizing an organic solvent, the third adhesive layer can also be laminated on the first adhesive layer, as in the second step. The laminating method and conditions are the same as those in the second step.
[0154] [Circuit connection structure and method for manufacturing the same]
[0155] Hereinafter, a circuit connection structure using the adhesive film 10 as a circuit connection material and a method for producing the same will be described.
[0156] Figure 2 Schematic cross-sectional view showing one embodiment of a circuit connection structure. Figure 2 As shown, the circuit connection structure 20 comprises: a first circuit component 13, having a first circuit substrate 11 and a first electrode 12 formed on a main surface 11a of the first circuit substrate 11; a second circuit component 16, having a second circuit substrate 14 and a second electrode 15 formed on a main surface 14a of the second circuit substrate 14; and a circuit connection portion 17, which is arranged between the first circuit component 13 and the second circuit component 16 and electrically connects the first electrode 12 and the second electrode 15 to each other.
[0157] The first circuit component 13 and the second circuit component 16 may be the same or different from each other. The first circuit component 13 and the second circuit component 16 may be a glass substrate or a plastic substrate with electrodes formed thereon; a printed circuit board; a ceramic circuit board; a flexible circuit board; an IC chip, etc. The first circuit substrate 11 and the second circuit substrate 14 may be formed of inorganic materials such as semiconductors, glass, and ceramics, organic materials such as polyimide and polycarbonate, and composite materials such as glass / epoxy.
[0158] The first electrode 12 and the second electrode 15 may be electrodes containing metals such as gold, silver, tin, ruthenium, rhodium, palladium, osmium, iridium, platinum, copper, aluminum, molybdenum, titanium, and oxides such as indium tin oxide (ITO), indium zinc oxide (IZO), and indium gallium zinc oxide (IGZO). The first electrode 12 and the second electrode 15 may also be electrodes formed by stacking two or more of these metals, oxides, and the like. The electrode formed by stacking two or more of these metals, oxides, and the like may have more than two layers or more than three layers. In the case where the first circuit component 13 is a plastic substrate, the first electrode 12 may be an electrode having a titanium layer on the outermost surface. The first electrode 12 and the second electrode 15 may be circuit electrodes or bump electrodes. At least one of the first electrode 12 and the second electrode 15 may be a bump electrode. In Figure 2 In this embodiment, the first electrode 12 is a circuit electrode and the second electrode 15 is a bump electrode.
[0159] The circuit connection portion 17 includes a cured product of the adhesive film 10. The circuit connection portion 17 may be composed of a cured product of the adhesive film 10. The circuit connection portion 17 includes, for example: a first cured product region 18, which is located on the first circuit component 13 side in the direction in which the first circuit component 13 and the second circuit component 16 are opposite to each other (hereinafter referred to as the "opposing direction") and is formed by a cured product of the (B) component, the (C) component, the (D) component, etc. in the first adhesive layer except for the conductive particles 4; a second cured product region 19, which is located on the second circuit component 16 side in the opposite direction and is formed by a cured product of the (D) component, etc. in the second adhesive layer; and conductive particles 4, which are at least interposed between the first electrode 12 and the second electrode 15 to electrically connect the first electrode 12 and the second electrode 15 to each other. As Figure 2 As shown, the circuit connection portion 17 may not have two distinct regions between the first cured material region 18 and the second cured material region 19 , but may form one cured material region by mixing the cured material derived from the first adhesive layer and the cured material derived from the second adhesive layer.
[0160] Figure 3 This is a schematic cross-sectional view showing one embodiment of a method for producing a circuit-connected structure. Figure 3 (a) and Figure 3 (b) is a schematic cross-sectional view showing each process. Figure 3 As shown, the manufacturing method of the circuit connection structure 20 includes the following steps: placing an adhesive film 10 between a first circuit component 13 having a first electrode 12 and a second circuit component 16 having a second electrode 15, and performing thermal compression bonding on the first circuit component 13 and the second circuit component 16 to electrically connect the first electrode 12 and the second electrode 15 to each other.
[0161] Specifically, if Figure 3As shown in (a), first, a first circuit component 13 including a first circuit substrate 11 and a first electrode 12 formed on a main surface 11a of the first circuit substrate 11 and a second circuit component 16 including a second circuit substrate 14 and a second electrode 15 formed on a main surface 14a of the second circuit substrate 14 are prepared.
[0162] Next, the first circuit member 13 and the second circuit member 16 are arranged so that the first electrode 12 and the second electrode 15 face each other, and the adhesive film 10 is arranged between the first circuit member 13 and the second circuit member 16. Figure 3 As shown in (a), the adhesive film 10 is laminated on the first circuit member 13 in such a manner that the first adhesive layer 1 side faces the main surface 11a of the first circuit substrate 11. Next, the second circuit member 16 is arranged on the first circuit member 13 laminated with the adhesive film 10 in such a manner that the first electrode 12 on the first circuit substrate 11 and the second electrode 15 on the second circuit substrate 14 face each other.
[0163] And, if Figure 3 As shown in (b), the first circuit component 13, the adhesive film 10 and the second circuit component 16 are heated and pressed in the thickness direction, thereby thermally pressing the first circuit component 13 and the second circuit component 16 together. Figure 3 As shown by the arrow in (b), since the second adhesive layer 2 has an uncured thermosetting component that can flow, it flows to fill the gaps between the second electrodes 15 and is cured by the above-mentioned heating. As a result, the first electrode 12 and the second electrode 15 are electrically connected to each other via the conductive particles 4, and the first circuit component 13 and the second circuit component 16 are bonded to each other, so that Figure 2 The circuit connection structure 20 shown. In the manufacturing method of the circuit connection structure 20 of the present embodiment, since a part of the first adhesive layer 1 can be said to be a layer cured by light irradiation, the conductive particles 4 are fixed in the first adhesive layer 1, and the first adhesive layer 1 hardly flows during the above-mentioned thermocompression bonding, and the conductive particles are effectively captured between the opposing electrodes, so that the connection resistance between the opposing first electrode 12 and the second electrode 15 can be reduced. In addition, by making the thickness of the first adhesive layer 5 μm or less, the fluidity of the conductive particles during circuit connection can be further suppressed.
[0164] The heating temperature during thermocompression bonding can be appropriately set, but for example, it can be 50 to 190°C. Regarding pressurization, there is no particular limitation as long as it is within the range that does not damage the adherend, but in the case of COP installation, for example, the area conversion pressure of the bump electrode can be 0.1 to 50 MPa. And in the case of COG installation, for example, the area conversion pressure on the bump electrode can be 10 to 100 MPa. These heating and pressurization times can be in the range of 0.5 to 120 seconds.
[0165] Example
[0166] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.
[0167] [Synthesis of resin]
[0168] (Production Example 1-1) Synthesis of Resin B1-1a
[0169] In a flask equipped with a stirring device, a condenser, a thermometer, and a gas inlet tube, 400.00 g of methyl ethyl ketone and 200.00 g of toluene as a solvent and 396.16 g of phenoxy resin (FX-293, manufactured by NIPPON STEEL Chemical & Material Co., Ltd.) were added and stirred until uniformly dissolved. Then, the temperature was raised to 60°C, and MOI-EG (2-(2-methacryloyloxyethoxy)ethyl isocyanate, R 1 3.80 g of a compound represented by formula (2) in which methyl is methyl, x is 2, and y is 2 (manufactured by SHOWA DENKOK.K.) and 0.04 g of dioctyltin dilaurate as a catalyst were added, and the mixture was stirred while blowing nitrogen gas into the flask to react for 2 hours, thereby obtaining the target resin B1-1a. 1 The modification rate was calculated from the integrated value of the peak in the obtained spectrum by H-NMR measurement. As a result, the modification rate of resin B1-1a was 1%.
[0170] (Production Example 1-2) Synthesis of Resin B1-1b
[0171] Resin B1-1b was obtained in the same manner as in Example 1-1 except that the charge amount of phenoxy resin was changed to 388.91 g and the charge amount of MOI-EG was changed to 11.05 g. The modification rate of resin B1-1b was 5%.
[0172] (Production Example 1-3) Synthesis of Resin B1-1c
[0173] Resin B1-1c was obtained in the same manner as in Example 1-1 except that the charge amount of phenoxy resin was changed to 380.50 g and the charge amount of MOI-EG was changed to 19.46 g. The modification rate of resin B1-1c was 9%.
[0174] (Production Example 1-4) Synthesis of Resin B1-1d
[0175] Resin B1-1d was obtained in the same manner as in Example 1-1 except that the charge amount of phenoxy resin was changed to 368.43 g and the charge amount of MOI-EG was changed to 31.53 g. The modification rate of resin B1-1d was 15%.
[0176] (Production Example 2-1) Synthesis of Resin B1-2a
[0177] In a flask equipped with a stirring device, a condenser, a thermometer, and a gas inlet tube, 400.00 g of methyl ethyl ketone and 200.00 g of toluene as a solvent and 396.16 g of a phenoxy resin (YP-70, manufactured by NIPPON STEEL Chemical & Material Co., Ltd.) were added and stirred until uniformly dissolved. Then, the temperature was raised to 60°C, 3.80 g of MOI-EG (2-(2-methacryloyloxyethoxy)ethyl isocyanate, manufactured by SHOWA DENKO KK) and 0.04 g of dioctyltin dilaurate as a catalyst were added, and the flask was stirred while blowing nitrogen gas, and the reaction was allowed to proceed for 2 hours, thereby obtaining the target resin B1-2a. As described above, the resin B1-2a was subjected to 1 The modification rate was calculated from the integrated value of the peak in the obtained spectrum by H-NMR measurement. As a result, the modification rate of resin B1-2a was 1%.
[0178] (Production Example 2-2) Synthesis of Resin B1-2b
[0179] Resin B1-2b was obtained in the same manner as in Example 2-1 except that the charge amount of phenoxy resin was changed to 381.66 g and the charge amount of MOI-EG was changed to 18.30 g. The modification rate of resin B1-2b was 5%.
[0180] (Production Example 2-3) Synthesis of Resin B1-2c
[0181] Resin B1-2c was obtained in the same manner as in Example 2-1 except that the charge amount of phenoxy resin was changed to 368.19 g and the charge amount of MOI-EG was changed to 31.77 g. The modification rate of resin B1-2c was 9%.
[0182] (Production Example 3-1) Synthesis of Resin B1-3a
[0183] In a flask equipped with a stirring device, a condenser, a thermometer, and a gas inlet tube, 400.00 g of methyl ethyl ketone and 200.00 g of toluene as a solvent and 388.91 g of phenoxy resin (FX-293, manufactured by NIPPON STEEL Chemical & Material Co., Ltd.) were added and stirred until uniformly dissolved. Then, the temperature was raised to 60°C, and AOI (2-(2-acryloyloxyethoxy)ethyl isocyanate, R 1 11.05 g of a compound represented by formula (2) in which 1 is hydrogen, x is 2, and y is 1 (manufactured by SHOWA DENKO KK) and 0.04 g of dioctyltin dilaurate as a catalyst were added, and the mixture was stirred while blowing nitrogen gas into the flask to react for 2 hours, thereby obtaining the target resin B1-3a. 1 The modification rate was calculated from the integrated value of the peak in the obtained spectrum by H-NMR measurement. As a result, the modification rate of resin B1-3a was 5%.
[0184] [Preparation of the first adhesive layer, the second adhesive layer, and the third adhesive layer]
[0185] The following materials were used to prepare the first adhesive layer, the second adhesive layer, and the third adhesive layer.
[0186] (A) Ingredients: Conductive particles
[0187] A-1: Conductive particles having an average particle size of 3.2 μm were used, the surface of the plastic core was nickel plated and the outermost surface was displacement plated with palladium.
[0188] (B) Component: Thermoplastic resin
[0189] Component (B1): a phenoxy resin in which at least a part of the hydroxyl groups are modified with a group represented by formula (1)
[0190] B1-1a: Resin of Production Example 1-1 (modification rate: 1%)
[0191] B1-1b: Resin of Production Example 1-2 (modification rate: 5%)
[0192] B1-1c: Resin of Production Example 1-3 (modification rate: 9%)
[0193] B1-1d: Resin of Production Example 1-4 (modification rate: 15%)
[0194] B1-2a: Resin of Production Example 2-1 (modification rate: 1%)
[0195] B1-2b: Resin of Production Example 2-2 (modification rate: 5%)
[0196] B1-2c: Resin of Production Example 2-3 (modification rate: 9%)
[0197] B1-3a: Resin of Production Example 3-1 (modification rate: 5%)
[0198] Component (B2): Thermoplastic resin other than component (B1)
[0199] B2-1: FX-293 (phenoxy resin, manufactured by NIPPON STEEL Chemical & Material Co., Ltd.)
[0200] B2-2: YP-70 (phenoxy resin, manufactured by NIPPON STEEL Chemical & Material Co., Ltd.)
[0201] B2-3: FX-310 (phenoxy resin, manufactured by NIPPON STEEL Chemical & Material Co., Ltd.)
[0202] B2-4: TOPR-300 (phenoxy resin, manufactured by NIPPON STEEL Chemical & Material Co., Ltd.)
[0203] B2-5: ZX1356-2 (phenoxy resin, manufactured by NIPPON STEEL Chemical & Material Co., Ltd.)
[0204] Component (C): Photocurable resin component
[0205] Component (C1): Radical polymerizable compound
[0206] C1-1: A-BPEF (ethoxylated naphthalene di(meth)acrylate (difunctional), manufactured by Shin-Nakamura Chemical Co., Ltd.)
[0207] C1-2: VR-90 (bisphenol A type epoxy (meth) acrylate (2-functional) (vinyl ester resin), manufactured by SHOWA DENKOK.K.)
[0208] Component (C2): Photoradical polymerization initiator
[0209] C2-1: IrgacureOXE-02 (compound having an oxime ester structure, manufactured by BASF)
[0210] (D) Component: Thermosetting resin component
[0211] Component (D1): Cationic polymerizable compound
[0212] D1-1: OXBP (oxetane compound, manufactured by UBE Corporation)
[0213] D1-2: OXSQ (oxetane compound, manufactured by TOAGOSEI CO., LTD.)
[0214] D1-3: EHPE3150 (alicyclic epoxy compound, manufactured by Daicel Corporation) D1-4: CEL2021P (alicyclic epoxy compound, manufactured by Daicel Corporation)
[0215] Component (D2): Thermal cationic polymerization initiator
[0216] D2-1: CXC-1821 (anilinium salt, manufactured by King Industries, Inc.)
[0217] Component (E): Coupling agent
[0218] ·E-1: SH-6040 (3-glycidoxypropyltrimethoxysilane, manufactured by Dow Corning Toray Co., Ltd.)
[0219] (F) Ingredients: Filler
[0220] F-1: R805 (silicon dioxide microparticles, manufactured by Evonik Industries AG)
[0221] F-2: SE2050 (silicon dioxide fine particles, manufactured by ADMATECHS COMPANY LIMITED)
[0222] <Preparation of the first adhesive film (first adhesive layer)>
[0223] The materials shown in Tables 1 and 2 were mixed according to the composition ratios shown in Tables 1 and 2 (the numerical values in Tables 1 and 2 refer to the amount of non-volatile components), and adhesive varnishes diluted with organic solvents were obtained. Then, the coating was performed on a demolding-treated PET (polyethylene terephthalate) film while applying a magnetic field, and the organic solvent was hot-air dried at 70°C for 5 minutes, thereby obtaining a composition layer formed by a composition containing each component. The thickness of the composition layers 1a to 1o after drying was 2μm, and the thickness of the composition layers 1p and 1q after drying was 6μm. Next, the composition layers 1a to 1q were irradiated with light (UV irradiation: metal halide lamp, cumulative light intensity: 1900 to 2300mJ / cm 2 ), thereby obtaining the first adhesive films (first adhesive layers) 1A to 1Q. The first adhesive films 1A to 1Q contain a cured product of a photocurable resin component and a thermosetting resin component. The thickness of the first adhesive films (first adhesive layers) 1A to 1O is 2 μm, and the thickness of the first adhesive films (first adhesive layers) 1P and 1Q is 6 μm.
[0224] [Table 1]
[0225]
[0226] [Table 2]
[0227]
[0228] <Preparation of the second adhesive film (second adhesive layer)>
[0229] The materials shown in Table 3 were mixed according to the composition ratio shown in Table 3 (the numerical values in Table 3 refer to the amount of non-volatile components), and an adhesive varnish diluted with an organic solvent was obtained. Then, it was applied on a PET (polyethylene terephthalate) film that had been subjected to a mold release treatment. The second adhesive film 2A was applied in a manner that the thickness after drying was 9 μm. The second adhesive film 2B was applied in a manner that the thickness after drying was 10 μm. The second adhesive film 2C was applied in a manner that the thickness after drying was 6 μm. Then, by drying the organic solvent, etc., the second adhesive films 2A to 2C containing each component were obtained. The constituent components of the second adhesive films 2A to 2C are the same.
[0230] [Table 3]
[0231]
[0232] <Third adhesive film (third adhesive layer)>
[0233] The materials shown in Table 4 were mixed in the composition ratio shown in Table 4 (the values in Table 4 refer to the non-volatile content), and an adhesive varnish diluted with an organic solvent was obtained. Then, it was applied on a release-treated PET (polyethylene terephthalate) film, and the organic solvent was dried to obtain a third adhesive film 3A. The third adhesive film 3A was applied so that the thickness after drying was 1 μm.
[0234] [Table 4]
[0235]
[0236] (Examples 1 to 9 and Comparative Examples 1 to 8)
[0237] [Manufacturing of adhesive film]
[0238] Adhesive films having the structures shown in Tables 5 and 6 were prepared using the first adhesive film, the second adhesive film, and the third adhesive film prepared as described above. For example, in the adhesive film of Example 1, the first adhesive film 1A was bonded to the second adhesive film 2A while applying a temperature of 50 to 60°C, and the release film of the first adhesive film 1A was peeled off. Then, the third adhesive film 3A was bonded to the first adhesive film 1A exposed by peeling off the release film while applying a temperature of 50 to 60°C, thereby obtaining the adhesive film of Example 1. As for the three-layer adhesive films of Examples 2 to 5, 8, 9 and Comparative Examples 1 to 4, 7, and 8, adhesive films having the structures shown in Tables 5 and 6 were prepared in the same manner as in Example 1. Regarding the two-layer adhesive films of Examples 6 and 7 and Comparative Examples 5 and 6, adhesive films having the structures shown in Tables 5 and 6 were prepared in the same manner as in Example 1 except that the third adhesive film was not attached.
[0239] [Measurement of Conductive Particle Density]
[0240] The adhesive films of Examples 1 to 9 and Comparative Examples 1 to 8 were measured at 20 locations every 25,000 μm using a microscope and image analysis software (trade name: ImagePro, manufactured by Hakuto Co., Ltd.). 2 The number of conductive particles per 1mm 2 The number of conductive particles was calculated to determine the conductive particle density. The results are shown in Tables 5 and 6.
[0241] [Localization evaluation of conductive particles]
[0242] The adhesive films of Examples 1 to 9 and Comparative Examples 1 to 8 were cut into a specified size (13 mm in length × 13 mm in width × about 12 μm in thickness) to prepare an evaluation film. Next, the evaluation film was attached to a polyimide substrate with aluminum wiring (substrate thickness: 50 μm, aluminum wiring thickness: 2 μm), and a semiconductor chip with gold bumps (chip size: 10.2 mm in length × 10.2 mm in width × 0.55 mm in thickness, bump height: about 9 μm, number of bumps: 184) was installed using a flip chip mounting device (trade name: FCB3-3, manufactured by Panasonic Corporation). The mounting conditions were set to a crimping head temperature of 190°C, a crimping time of 10 seconds, and a crimping pressure of 30 MPa. Thus, a semiconductor device in which a polyimide substrate with aluminum wiring and a semiconductor chip with gold bumps were daisy-chained was prepared. The semiconductor chip of the produced semiconductor device was peeled from the substrate using a shear force measuring apparatus, and the degree of localization of the conductive particles remaining in the evaluation film on the semiconductor chip was observed and evaluated based on the following criteria. The results are shown in Tables 5 and 6.
[0243] A Judgment: The area of the region without conductive particles is less than 1% of the area of the semiconductor chip
[0244] B Judgment: The area of the region without conductive particles is 1% or more and less than 15% of the area of the semiconductor chip
[0245] C: The area of the region without conductive particles is 15% or more relative to the area of the semiconductor chip.
[0246] [Evaluation of connection resistance]
[0247] (Preparation of circuit components)
[0248] As the first circuit component, a component with a Ti (50 nm) / Al (400 nm) wiring pattern (pattern width: 19 μm, inter-electrode space: 5 μm) formed on the surface of a polyimide substrate (outer shape: 38 mm × 28 mm, thickness: 50 μm) was prepared. As the second circuit component, an IC chip (outer shape: 0.9 mm × 20.3 mm, thickness: 0.3 mm, bump electrode size: 70 μm × 12 μm, inter-bump electrode space: 12 μm, bump electrode thickness: 9 μm) was prepared in which gold bump electrodes were arranged in two rows in a staggered manner.
[0249] (Fabrication of circuit connection structure)
[0250] Using the adhesive films of Examples 1 to 9 and Comparative Examples 7 and 8 that were judged A or B in the evaluation of the localization of the conductive particles, a circuit connection structure was produced. The adhesive film was arranged on the first circuit component so that the first adhesive layer or the third adhesive layer of the adhesive film was in contact with the first circuit component. A thermal compression bonding device (BS-17U, manufactured by OHASHI ENGINEERING Co., Ltd.) including a workbench including a ceramic heater and a tool (8 mm × 50 mm) was used at 70°C and 0.98 MPa (10 kgf / cm 2 ) for 2 seconds to attach the adhesive film to the first circuit component, and peel off the release film on the side of the adhesive film opposite to the first circuit component. Next, after aligning the position of the bump electrode of the first circuit component with the circuit electrode of the second circuit component, heat and pressurize for 5 seconds under the conditions of the maximum measured temperature of the adhesive film of 160°C and the area conversion pressure of the bump electrode of 20MPa, and attach the second adhesive layer of the adhesive film to the second circuit component, thereby manufacturing a circuit connection structure.
[0251] (Evaluation of connection resistance)
[0252] The connection resistance was evaluated using the obtained circuit connection structure. The connection resistance was evaluated by a four-terminal measurement method, and the average value of the connection resistance values at 14 locations was used for evaluation. A digital multimeter (7461A, manufactured by ADC CORPORATION) was used in the measurement. The case where the connection resistance value was less than 1.0Ω was evaluated as A judgment, the case where the connection resistance value was greater than 1.0Ω and less than 2.0Ω was evaluated as B judgment, and the case where the connection resistance value was greater than 2.0Ω was evaluated as C judgment. The results are shown in Tables 5 and 6.
[0253] [Table 5]
[0254]
[0255] [Table 6]
[0256]
[0257] As shown in Tables 5 and 6, the adhesive films of Examples 1 to 9 were excellent in both the evaluation of localization of conductive particles and the evaluation of connection resistance. Thus, it was confirmed that the adhesive film of the present invention can suppress the localization of conductive particles and reduce the connection resistance even when heat and external force are applied.
[0258] Explanation of symbols
[0259] 1-first adhesive layer, 2-second adhesive layer, 4-conductive particles, 5-adhesive component, 10-adhesive film for circuit connection (adhesive film), 11-first circuit substrate, 12-first electrode (circuit electrode), 13-first circuit component, 14-second circuit substrate, 15-second electrode (bump electrode), 16-second circuit component, 17-circuit connection portion, 20-circuit connection structure.
Claims
1. An adhesive film for circuit connection, comprising: The first adhesive layer contains conductive particles and a thermoplastic resin; and a second adhesive layer disposed on the first adhesive layer, The thermoplastic resin includes a phenoxy resin in which at least a part of the hydroxyl groups are modified with a group represented by the following formula (1) or the following formula (1A). In formula (1), R 1 represents a hydrogen atom or a methyl group, x represents an integer of 2 to 6, y represents an integer of 1 to 6, * represents a bonding position to an oxygen atom derived from a hydroxyl group, In formula (1A), R 1 , x, y and * have the same meanings as described above, and *1 and *2 represent the bonding positions to the carbon atoms of other radical polymerizable groups.
2. The circuit connection adhesive film according to claim 1, wherein: The thickness of the first adhesive layer is 5 μm or less, A ratio of the thickness of the first adhesive layer to the average particle diameter of the conductive particles is 0.50 or more.
3. The circuit connection adhesive film according to claim 1, wherein: The first adhesive layer further contains a cured product of a photocurable resin component and a first thermosetting resin component. The second adhesive layer further contains a second thermosetting resin component.
4. The circuit connection adhesive film according to claim 3, wherein: The photocurable resin component includes a radical polymerizable compound and a photoradical polymerization initiator.
5. The circuit connection adhesive film according to claim 4, wherein: The first thermosetting resin component and the second thermosetting resin component include a cationically polymerizable compound and a thermal cationic polymerization initiator.
6. The circuit connection adhesive film according to claim 5, wherein: The cationically polymerizable compound is at least one selected from the group consisting of oxetane compounds and alicyclic epoxy compounds.
7. The circuit connection adhesive film according to claim 5, wherein: The thermal cationic polymerization initiator is a salt compound having an anion containing boron as a constituent element.
8. The circuit connection adhesive film according to claim 3, further comprising: The third adhesive layer is provided on the side of the first adhesive layer opposite to the second adhesive layer and contains a third thermosetting resin component.
9. The circuit-connecting adhesive film according to claim 8, wherein: The third thermosetting resin component includes a cationically polymerizable compound and a thermal cationic polymerization initiator.
10. A method for manufacturing a circuit connection structure, comprising the following steps: The circuit connection adhesive film according to any one of claims 1 to 9 is interposed between a first circuit component having a first electrode and a second circuit component having a second electrode, and the first circuit component and the second circuit component are thermally pressed to electrically connect the first electrode and the second electrode to each other.
11. A circuit connection structure comprising: A first circuit component having a first electrode; a second circuit component having a second electrode; and a circuit connection portion disposed between the first circuit member and the second circuit member and electrically connecting the first electrode and the second electrode to each other; The circuit connection portion includes a cured product of the circuit-connecting adhesive film according to any one of claims 1 to 9.
Citation Information
Patent Citations
Connection body, manufacturing method therefor, electronic component connection method and electronic component
JP2016054288A